2016
DOI: 10.1016/j.chom.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Genes Enhance Murine Gammaherpesvirus 68 Reactivation from Latency by Preventing Virus-Induced Systemic Inflammation

Abstract: SUMMARY Host genes that regulate systemic inflammation upon chronic viral infection are incompletely understood. Murine γ-herpesvirus 68 (MHV68) infection is characterized by latency in macrophages, and reactivation is inhibited by Interferon-γ (IFN-γ). Using a Lysozyme-M-cre (LysMcre) expression system, we show that deletion of autophagy-related (Atg) genes Fip200, beclin 1, Atg14, Atg16L1, Atg7, Atg3, and Atg5, in the myeloid compartment, inhibited MHV68 reactivation in macrophages. Atg5-deficiency did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 86 publications
1
60
0
1
Order By: Relevance
“…Mice were latently infected with the γ-herpesvirus MHV68 and the ability of MHV68 to reactivate from PECs was evaluated (36,37). We found no difference in viral reactivation from latently infected LysMD3 WT or LysMD3-deficient PECs ( Figure 7B and Figure 7C).…”
Section: Lack Of a Role For Mlysmd3 In Response To Viral Infectionmentioning
confidence: 88%
See 2 more Smart Citations
“…Mice were latently infected with the γ-herpesvirus MHV68 and the ability of MHV68 to reactivate from PECs was evaluated (36,37). We found no difference in viral reactivation from latently infected LysMD3 WT or LysMD3-deficient PECs ( Figure 7B and Figure 7C).…”
Section: Lack Of a Role For Mlysmd3 In Response To Viral Infectionmentioning
confidence: 88%
“…MHV68 WUMS (ATCC VR1465) was used and reactivation from latency was measured as described (36,37,77). Mice were infected with 1e6 PFU MHV68 IP and after 16 days, PECs or spleens were pooled from 3-5 mice and serial dilutions of cells were plated on a MEF monolayer.…”
Section: Lps Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atgs exert a concerted effect in autophagy, i.e., autophagosome initiation and elongation and lysosomal functions (28). Various Atgs play diverse roles in innate and inflammatory responses, such as the eradication of intracellular pathogens, murine gammaherpesvirus 68 reactivation from latency, Ag presentation, and innate immune signaling in a cell type-specific manner (28,35,36). Despite these findings, research on the molecular mechanisms of Atg regulation in macrophages during infection is in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an essential cellular process whereby cytoplasmic cargo, and sometimes a pathogen, is engulfed in a double-membranebound vesicle, termed the autophagosome, that fuses to the lysosome for degradation. We recently reported that multiple Atg genes in myeloid cells regulate systemic inflammation, and especially IFN-␥, thus inhibiting viral reactivation (17). In the absence of Atg genes, MHV68 fails to reactivate efficiently, and neutralization of IFN-␥ partially reverses this defect.…”
Section: Systemic Inflammation and Reactivationmentioning
confidence: 99%